Pengaruh Budaya Organisasi dan Organizational Citizenship Behavior (OCB) terhadap Kinerja Pegawai Rumah Sakit Tk. III Baladhika Husada Jember - Nisa, Desy Khoirun; Santoso, Budi; Azhad, M. Naely (International Journal of Social Science and Business, 2018)
This research aim to analyze the effect of organizational cultural and organizational citizenship behavior (OCB) to work performance at Baladhika Husada Jember 3rd Level Hospital. Data used in this research is primary data was collected by questionnaire. The population of this research is all employee of Baladhika Husada Jember 3rd Level Hospital amount of 98 peoples, included doctor, nurse, also administration and human resources. Determination of samples using total sampling. The analyze technique used multiple linier regressions analysis. The result of hypothesis testing shown that the organizational cultural has significant effect to work performance at Baladhika Husada Jember 3rd Level Hospital or H1 accepted. Organizational citizenship behavior (OCB) has significant effect to work performance at Baladhika Husada Jember 3rd Level Hospital or H2 accepted.